LONG-TERM RESULTS OF MERIDIONAL СYCLODIALYSIS AB INTERNO WITH IMPLANTATION OF A SUPRACILIARY METALIC IMPLANT IN DECREASING INTRAOCULAR PRESSURE IN GLAUCOMA PATIENTS - Ахмад Салех Солиман Шрадка; Винод Шарванович Кумар; Михаил Александрович Фролов; Галина Николаевна Душина; Андрей Игоревич Беззаботнов (Медицина в Кузбассе, 2019)
Purpose – to analyze long-term results of meridional cyclodialysis ab interno (MCai) with implantation of a supraciliary metalic implant (SMI) in decreasing intraocular pressure (IOP) in patients with glaucoma.